2020
DOI: 10.15252/emmm.201910941
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of chromosome instability is a mechanism to evade oncogene addiction

Abstract: Chromosome instability (CIN) has been associated with therapeutic resistance in many cancers. However, whether tumours become genomically unstable as an evolutionary mechanism to overcome the bottleneck exerted by therapy is not clear. Using a CIN model of Kras‐driven breast cancer, we demonstrate that aneuploid tumours acquire genetic modifications that facilitate the development of resistance to targeted therapy faster than euploid tumours. We further show that the few initially chromosomally stable cancers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 36 publications
4
37
0
Order By: Relevance
“…Therefore, the propagation of CIN in cancer can arise through inactivation or bypass of the p53 pathway and the acquisition of mechanisms that allow tolerance of replication stress and aneuploidy-associated stressors, such as activation of the proteasome and autophagy and CIN adaptation [198,229,231]. While low and moderate levels of CIN may allow the evolution of advantageous karyotypes and the emergence of genomic alterations that provide resistance to therapy, tumors may not tolerate high CIN levels [232][233][234][235][236][237][238]. Interestingly, it has been reported that, in addition to acquiring CIN tolerance, tumors undergo CIN attenuation or buffering.…”
Section: Emerging Concepts: Chromosomal Instability/aneuploidy Toleramentioning
confidence: 99%
“…Therefore, the propagation of CIN in cancer can arise through inactivation or bypass of the p53 pathway and the acquisition of mechanisms that allow tolerance of replication stress and aneuploidy-associated stressors, such as activation of the proteasome and autophagy and CIN adaptation [198,229,231]. While low and moderate levels of CIN may allow the evolution of advantageous karyotypes and the emergence of genomic alterations that provide resistance to therapy, tumors may not tolerate high CIN levels [232][233][234][235][236][237][238]. Interestingly, it has been reported that, in addition to acquiring CIN tolerance, tumors undergo CIN attenuation or buffering.…”
Section: Emerging Concepts: Chromosomal Instability/aneuploidy Toleramentioning
confidence: 99%
“…Chromosomal changes at the individual development are usually highlighted as catastrophic genomic events, while such chromosomal alterations often result in carcinogenesis and infertility [8,9]. Genomes of carcinogenetic cells are highly dynamic, and in some cases, chromosomal changes, either induced or spontaneous, lead to therapeutic resistance [10]. Chromoanagenesis, encompasses chromothripsis, chromoanasynthesis and chromoplexy, and was recently described as a possible mechanism contributing to chromosomal evolution [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear to what extent the aneuploidy that arises during tumorigenesis functions as a driver of cancer progression, and to what extent aneuploidy occurs simply as a byproduct of the loss of checkpoint control that often occurs in advanced malignancies. Previous studies have shown that CIN can accelerate the adaptation to oncogene withdrawal in mouse models of KRAS and BRAF driven cancers, which often displayed recurrent aneuploidies 33,34 . Similarly, our work shows that CIN can drive the evolution of drug-resistant cells with recurrent aneuploidies, and it demonstrates that one such aneuploidy is sufficient to confer drug resistance.…”
Section: Discussionmentioning
confidence: 99%